1996
DOI: 10.1002/(sici)1096-9063(199606)47:2<125::aid-ps394>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the New Herbicide KIH-6127. Part I. Novel Synthesis of Methyl 6-Acetylsalicylate as a Key Synthetic Intermediate for the Preparation of 6-Acetyl Pyrimidin-2-yl Salicylates and Analogues

Abstract: A novel synthesis of methyl 6-acetylsalicylate as a key synthetic intermediate for methyl 2-[(4,6-dimethoxypyrimidin-2-yl)oxy]-6-[l-(methoxyimino) ethyllbenzoate (KIH-6127) was studied, and directed at 6-substituted pyrimidin-2-yl salicylate herbicides and their analogues. Three synthetic approaches were successful: a modification of the Sandmeyer reaction of 6-acetylanthranilate (Method A), a direct ring-opening reaction of 3-methylphthalide using potassium permangamate and magnesium nitrate (Method B), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Among them, methoxy compound (1) exhibited the highest activity. Cyano (2), methylthio (3), nitro (4) and thiocyano (5) analogues also exhibited excellent herbicidal activity in this order. Carboxylic acid derivatives, such as (6) and 7, and the alkyl(aryl)oxy compounds such as (8), (9), (10), (11) and 12exhibited moderate herbicidal activity.…”
Section: Lead Compound Generationmentioning
confidence: 85%
“…Among them, methoxy compound (1) exhibited the highest activity. Cyano (2), methylthio (3), nitro (4) and thiocyano (5) analogues also exhibited excellent herbicidal activity in this order. Carboxylic acid derivatives, such as (6) and 7, and the alkyl(aryl)oxy compounds such as (8), (9), (10), (11) and 12exhibited moderate herbicidal activity.…”
Section: Lead Compound Generationmentioning
confidence: 85%
“…The title compound was synthesized according to the literature procedure of Tamaru & Saito (1996). Crystals appropriate for data collection were obtained by slow evaporation of an isopropyl ether solution at 298 K.…”
Section: Methodsmentioning
confidence: 99%
“…The title compound, (I) ( Fig. 1), is a key intermediate in the synthesis of pesticides such as the herbicide KIH-6127 (Tamaru & Saito, 1996). In this paper, we report the results of an X-ray diffraction study of this compound, as its monohydrate.…”
Section: Commentmentioning
confidence: 97%
“…S1), is composed of a mixture of its (E) -isomer (I) and (Z) -isomer (II) as the active ingredient due to its chemical structure contain oxime (Song et al 2010), a mixture of two isomers (I and II) in a > 9:1 (major/minor) ratio which was developed from sulfonylurea by Kumiai Chemical Industry Co., Ltd. In 1996 (Tokyo, Japan) (Tamaru and Saito 1996). Tamaru et al (1997)) reported that (E) -isomer (I) has been confirmed to restrain the plant enzyme acetolactate synthase (ALS) and prevent branched chain amino acid biosynthesis, and the (E) -pyriminobac-methyl (EPM) showed stronger soil adsorption and weaker hydrophilic properties than (Z) -pyriminobac-methyl (ZPM), thus EPM was selected as the best compound to develop a commercial weedicide, which is commonly used to control the growth of sedges and both gramineous and annual weeds.…”
Section: Introductionmentioning
confidence: 99%